Dampak Pencahayaan terhadap Kualitas Warna Ikan Nemo (Amphiprion percula) - Tampani, Siprianus; Lukas, Ade Yulita Hesti; Liufeto, Franchy Ch (Nusa Cendana University, 2024)
This study lasted for 30 days in the Laboratory of the Faculty of Animal Husbandry, Marine and Fisheries. This study used a Completely Randomized Design (CRD) with three treatments and three replications, consisting of treatment A lighting for 24 hours, treatment B lighting for 12 hours and treatment C without lighting. The parameters observed in this study were the brightness of the orange and white colors on the body of the nemo fish, as well as water quality data. The results showed that the quality of the orange and white colors on the body of the nemo fish increased with the length of lighting time. The results of the ANOVA test showed that the treatment of the length of lighting time had a significant effect on the brightness of the orange and white colors in the nemo fish. Treatment A with lighting for 24 hours showed the quality of the orange color with a score of 3.5 ± 0.17b and white 3.0 ± 0.0c which was better than treatments B and C. While the lowest quality of orange and white colors occurred in treatment C (without lighting) namely orange with a score of 2.2 ± 0.17a and white with a score of 2.0 ± 0.0a. Keywords: Nemo fish, exposure time, orange, white.